Solar power as remunerative crop - Shah, Tushaar; Durga, Neha; Verma, Shilp; Rathod, Rahul (International Water Management Institute, 2016)
Anand, the small Gujarat town that gave India its dairy cooperave movement, has now spawned a new cooperave that may well grow into a genre of its own. The Dhundi Solar Pump Irrigators' Cooperave